Laser wavelength dependence of background fluorescence in Raman spectroscopic analysis of synovial fluid from symptomatic joints. (1st July 2013) - Yang, Shan; Li, Bolan; Slipchenko, Mikhail N.; Akkus, Anna; Singer, Nora G.; Yeni, Yener N.; Akkus, Ozan
Abstract : Gout is a disease process where the nucleation and growth of crystals in the synovial fluid of joints elicit painful arthritis‐like symptoms. Raman spectroscopy is evolving as a potential diagnostic tool in identifying such crystals; however, attainment of sufficient Raman signal while overcoming the background fluorescence remains as a major challenge. The current study focused on assessing whether excitation in 532–700 nm range will provide greater signal intensity than the standard 785 nm while not being impeded by background fluorescence. We characterized the fluorescence spectra, absorption spectra and Raman spectra of synovial fluid from patients who presented 'gout‐like symptoms' (symptomatic) and controls (asymptomatic). A digestion and filtration method was developed to isolate crystals from synovial fluid while reducing the organic burden. Spectral profile and photobleaching dynamics during Raman spectroscopy were observed under an excitation wavelength range spanning 532 to 785 nm. Absorbance and fluorescence profiles indicated the digestion and filtration worked effectively to extract crystals from symptomatic synovial fluid without introducing additional fluorescence. Raman spectral analyses at 532 nm, 660 nm, 690 nm and 785 nm indicated that both asymptomatic and symptomatic samples had significant levels of fluorescence at excitation wavelengths below 700 nm, which either hindered the collection of Raman signal or necessitated prolonged durations of photobleaching. Raman‐based diagnostics were more feasible at the longest excitation wavelength of 785 nm without employing photobleaching. This study further demonstrated that a near‐infrared (NIR) OEM‐based lower‐cost Raman system at 785 nm excitation has sufficient sensitivity to identify crystals isolated from the synovial fluid. In conclusion, while lower excitation wavelengths provide greater signal, the fluorescence necessitates NIR wavelengths for Raman analysis of crystal species observed in synovial aspirates. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The current study investigated the fluorescence from asymptomatic and symptomatic synovial aspirates in the context of Raman‐based diagnosis of crystals leading to arthritic symptoms in the joint space. It was demonstrated that filtering of the samples following enzymatic digestion allowed the utilization of an inexpensive Raman set‐up using OEM‐based off‐the shelf components. In addition, we showed that the Raman signal can be recovered from crystals at 785 nm laser excitation without being masked by background fluorescence from the organic phase.